2017
DOI: 10.1038/ncomms15843
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of thermal rectification in suspended monolayer graphene

Abstract: Thermal rectification is a fundamental phenomenon for active heat flow control. Significant thermal rectification is expected to exist in the asymmetric nanostructures, such as nanowires and thin films. As a one-atom-thick membrane, graphene has attracted much attention for realizing thermal rectification as shown by many molecular dynamics simulations. Here, we experimentally demonstrate thermal rectification in various asymmetric monolayer graphene nanostructures. A large thermal rectification factor of 26% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
193
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(202 citation statements)
references
References 39 publications
(48 reference statements)
6
193
3
Order By: Relevance
“…Theoretical models to realize various types of thermal devices have been developed . Because of the advantages of high thermal conductivity, single‐atom thickness and tunable shape, graphene‐based thermal rectifier and thermal modulator have been explored both theoretically and experimentally.…”
Section: Phonon‐driven Emerging Applications Of 2d Semiconductorsmentioning
confidence: 99%
“…Theoretical models to realize various types of thermal devices have been developed . Because of the advantages of high thermal conductivity, single‐atom thickness and tunable shape, graphene‐based thermal rectifier and thermal modulator have been explored both theoretically and experimentally.…”
Section: Phonon‐driven Emerging Applications Of 2d Semiconductorsmentioning
confidence: 99%
“…Since the first observation of thermal rectification by Starr in 1936, thermal rectification has been realized through various mechanisms: asymmetric nanostructured geometry, evaporation/condensation, infrared emission, temperature dependence of thermal conductivity, mechanical tensile strain and an imperfect interface junction, as well as nonlinear lattice models, as reviewed in the literature . Based on the mechanism of the temperature dependence of thermal conductivity, a thermal diode can be realized by coupling two materials with different temperature dependences of thermal conductivities.…”
Section: Applications Of Pcms With Tuned Thermal Conductivitymentioning
confidence: 99%
“…In addition to studying the influence of shape on the thermal rectification characteristics of graphene, suspended graphene can also show good thermal rectification characteristics due to the influence of its own strain. In 2017, Wang et al experimentally demonstrated thermal rectification in various asymmetric monolayer graphene nanostructures ( Figure ). A large thermal rectification factor of 26% was achieved in a defect‐engineered monolayer graphene with nanopores on one side.…”
Section: Uncoupled Thermal Devicementioning
confidence: 99%
“…The solid lines are the theoretical predictions based on a lattice dynamics model. Reproduced under the terms and conditions of the Creative Commons Attribution 4.0 International License . Copyright 2017, Springer Nature.…”
Section: Uncoupled Thermal Devicementioning
confidence: 99%